The Influence of Marketing Strategy and Product Innovation on Purchasing Decisions with Competitive Advantage as an Intervening Variable on South Sumatra Fertilizer Consumers - Luthfia; Ahmad Maulana; Aslamia Rosa (JURNAL ECONOMINA, 2026)
his study aims to analyze the influence of marketing strategy and product innovation on purchasing decisions with competitive advantage as an intervening variable among Pusri NPK Fertilizer consumers in South Sumatra. The study used a quantitative method with an explanatory research approach. The population in this study were end users of specific innovation products, Cassava NPK Fertilizer and Coffee NPK Fertilizer, who purchased commercially in the South Sumatra region in 2022–2025. The sampling technique used purposive sampling with a sample size of 165 respondents. Data collection was carried out through questionnaires using Google Forms. Data analysis used the Partial Least Square- Structural Equation Modeling (PLS-SEM) method. The results showed that marketing strategy had a significant effect on competitive advantage, product innovation had a significant effect on competitive advantage, competitive advantage had a significant effect on purchasing decisions, and product innovation had a significant effect on purchasing decisions. However, marketing strategy did not have a significant direct effect on purchasing decisions. The findings of this study indicate that competitive advantage can be an intervening variable that strengthens the relationship between marketing strategy and product innovation on purchasing decisions of Pusri NPK Fertilizer consumers in South Sumatra.